Pendidikan Multikultural Dalam Perspektif Islam - Nuri Indah Sari; Tri Wulan Sari; Edvina Syahnanda; Khadijah Khadijah; Ahmad Darlis (Jurnal Ilmiah Wahana Pendidikan, 2023)
In general, this research aims to determine the concept of multicultural education in an Islamic perspective. In particular, this research in aimed at understanding the concept of multicultural education from the perspective of the Qur'an and Hadith as well to find out the values of multicultural education contained in the Qur'an and Hadith. This study uses the library research type method (library research),namely research referring to books or library sources (references) related to the discussion. In this study, the results obtained data that multicultural education is in line with Islamic values. As exemplified by the Prophet Muhammad Saw. and his friends in Medina that Islam really appreciates differences and there are many arguments that explain tolerance of differences.